66 Ethnic differences in carotid intimal medial thickness and carotid-femoral pulse wave velocity are present in UK children. (9th June 2011) - Whincup, P H; Nightingale, C M; Rapala, A; Joysurry, D; Prescott, M; Donald, A E; Ellins, E; Donin, A; Masi, S; Owen, C G; Rudnicka, A R; Cook, D G; et al.
Abstract : Introduction: There are marked ethnic differences in cardiovascular disease risks in UK adults; South Asians have high risks of coronary heart disease and stroke while black African-Caribbeans have high risks of stroke and slightly low risks of coronary heart disease when compared with white Europeans. Ethnic differences in cardiovascular risk factors are apparent in childhood, but little is known abut ethnic differences in vascular structure and function during childhood. We set out to measure two vascular markers of cardiovascular risk, common carotid intimal-medial thickness (cIMT) and carotid-femoral pulse wave velocity (PWV) in UK children from different ethnic groups. Methods: We conducted a school-based study examining the cardiovascular risk profiles of 9–10 year-old UK children, including similar numbers of South Asian, black African-Caribbean and white European participants. Following a baseline cardiovascular risk survey with measurements of body build, blood pressure, fasting blood lipids, insulin and HbA1c, 1400 children were invited to have measurements of cIMT (bilateral measurements were made with a Zonare ultrasound scanner). A subgroup of these children (n=900) was also invited for PWV measurements, made with a Vicorder device. All analyses were adjusted for age, gender and allowed for clustering at school level. Results: In all, 939 children (67% response) had measurements of cIMT and 631 children (70% response) had measurements of PWV. Mean cIMT was 0.475 mm (SD 0.035 mm); mean PWV was 5.2 m/s (SD 0.7 m/s). Compared with white European children, black African-Caribbeans had higher cIMT (mean difference 0.014 mm, 95%CI 0.008 to 0.021 mm) and PWV (% difference 3.3, 95%CI 0.4 to 6.2); South Asian children had similar cIMT to white Europeans but slightly higher PWV (% difference 2.7, 95%CI −0.1 to 5.5%). cIMT was positively associated with systolic and diastolic blood pressure but not with other cardiovascular risk markers. In contrast, PWV was positively associated with adiposity, diastolic blood pressure and insulin resistance. Black African-Caribbean children had lower LDL-cholesterol levels and higher insulin and HbA1c levels than white Europeans; South Asian children had higher insulin, HbA1c and triglyceride levels. However, adjustment for these risk factors had little effect on the ethnic differences in cIMT and PWV observed. Conclusions: Ethnic differences in cIMT and PWV, markers of long-term cardiovascular risk, are apparent in childhood. These differences are not fully explained by the ethnic differences in established cardiovascular risk markers observed. The results suggest that there may be important opportunities for prevention of cardiovascular disease before adult life, particularly in high-risk ethnic minority groups.